An extensive review on block chain - Ravendra Kumar,; Dhara Upadhyay,; Poonam Agarwal,; Rathore, Janvi (International Journal of Psychosocial Rehabilitation, 2020)
The blockchain technology is the most recent technology in the current monetary system. Blockchain technology arranges blocks separately identified linked transaction history into a chain. As it is a chain it includes the order of blocks. It would be beneficial as it is reliable. Also, it can be making use like assured money transactions, tracing items and make cocksure of data veracity. Blockchain makes it almost impossible to hack transactions. A huge number of industries can benefit from this growing technology as it has the ability to make a cheap cost by gathering the processes and breaking form or paperwork.